The Impact of Social Media Marketing on Consumers' Online Clothing Purchase Intention during COVID in Azerbaijan - Babayeva, Aytaj (ADA University, 2022)
This research study aimed to explore the impact of social media marketing (SMM) on consumers’ online clothing purchase intention during COVID-19 in Azerbaijan. In comparison to most existing literature reviews, this study is dedicated to the explanation of the branding process that occurs on various social media platforms. For this purpose, different social media-based branding components, namely brand trust, brand awareness, brand community, interaction, emotional attachment, and e-WOM were combined to measure their impact on online clothing purchase intention in Azerbaijan. Considering previous studies did not demonstrate how these factors affect purchase intention, and similar research has not been conducted in Azerbaijan, this research carries more significance, and it will have a significant contribution to the existing literature reviews. The data was collected from the people living in Baku and the analysis was conducted using this data to identify a correlation between these variables. It was found that there is a positive and statistically significant relationship between SMM antecedents (brand trust, brand community, and brand awareness) and online clothing purchase intention. On the other hand, the result of the study helps us to conclude that there is a negative relationship between other social media branding items (emotional attachment, e-WOM, and interaction) and online clothing buying intention during COVID-19 in Azerbaijan. Furthermore, it has been assumed that some variables can affect the strength of this relationship; therefore, research controlled their effect. As a result, it has been determined that the inclusion of these control variables (age, gender, and income) did not change the outcome.
Keywords: Social Media Marketing.; Purchase intention.; Brand trust.; Electronic Word-of-Mouth (e-WOM).; Business